Do radiologists still need to report chest x rays?. Issue 1005 (5th July 2009) - Mehrotra, P; Bosemani, V; Cox, J
Abstract : Objective: Chest x rays (CXRs) are among the most difficult radiographs to interpret accurately. The aim of this study was to assess the ability of different grades and specialities of clinicians to evaluate a series of CXRs correctly. Methods: 60 clinicians of different grades and from different specialities were randomly recruited to interpret 15 CXRs within 30 min. Radiographs included normal (n = 5) and abnormal images of common medical emergencies (n = 10). Non-parametric statistical tests examined for significant differences in the ability of different grades and specialities of doctors to interpret CXRs. Results: Senior doctors (consultants and registrars, n = 32) attained significantly higher scores than junior doctors (senior house officers, foundation 1 and 2 doctors, n = 28, p = 0.001). Specialists (consultants and registrars in radiology and respiratory medicine, n = 7) achieved significantly higher scores than non-specialists (all other consultants and registrars, n = 25, p = 0.0002). In addition, senior radiologists (consultants and registrars) attained significantly higher scores than senior doctors from other specialities (p = 0.002). Conclusion: To improve patient care, we suggest that all chest x rays should be reviewed at an early stage during a patient's hospital admission by a senior clinician and reported by a radiologist at the earliest opportunity. We also suggest that structured teaching on CXR interpretation should be made available for newly qualified doctors, especially with the introduction of shortened training.